2019
DOI: 10.1088/1755-1315/394/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Soil Disturbance by Logging Operation of Industrial Plantation Forest in Indonesia

Abstract: Logging concessions in natural forest and industrial plantation forest are the main producers of logs in Indonesia. Several companies of industrial plantation forest have been successfully planted with fast-growing species such as Acacia mangium for pulpwood. These plantation forests have entered their annual harvesting period. Some options of timber harvesting machines such as forwarder, harvester, feller buncher, and excavator are chosen to remove timber from stump to the log landing site. The negative impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In addition to the rather steep field conditions, the operator's error was also not maximized when using the shear head. In comparison to manual felling with a chainsaw, the stumps range in height from 2 cm to 19 cm and the average volume of waste per tree is 0.0034 m 3 , as reported in reference [10].…”
Section: Stump Wastementioning
confidence: 88%
See 1 more Smart Citation
“…In addition to the rather steep field conditions, the operator's error was also not maximized when using the shear head. In comparison to manual felling with a chainsaw, the stumps range in height from 2 cm to 19 cm and the average volume of waste per tree is 0.0034 m 3 , as reported in reference [10].…”
Section: Stump Wastementioning
confidence: 88%
“…IOP Publishing doi:10.1088/1755-1315/1282/1/012002 2 Felling and skidding are part of the harvesting activities which usually require the use of heavy equipment. The impact caused by using heavy equipment generally occurs blading and soil compaction [10,11]. Until now, it can be stated that the use of wood in East Kalimantan is still inefficient due to the large quantity of wood waste left in the forest.…”
Section: Introductionmentioning
confidence: 99%
“…The use of heavy equipment in log extraction also could damage the soil. The movement of the bulldozer to skid the log would open the forest area and disturb natural regeneration and soil (Matangaran et al 2019a;Matangaran et al 2019b). Therefore, some improvements have been proposed by Hendrison (1990) to minimize the damage of selective logging on the vegetation, such as improved planning and organization of road networks, controlled directional felling and controlled skidding, and log extraction by winching.…”
Section: Introductionmentioning
confidence: 99%
“…The scale of forest stand damage caused by logging operations depends on the intensity of timber harvesting (Matangaran et al 2019b). Although there have been several studies investigating the impacts of logging on vegetation and the stand structure of the forest, adding more research might be useful to enrich our understanding of this issue, especially in the context of tropical forests in Kalimantan, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The change in carbon stock [5,6,7] and ground biomass is caused by log extraction from the natural forest [8,9]. Machines such as bulldozers showed that soil compaction occurs due to heavy equipment operations in forest harvesting [10,11). The amount of forest stand damage that occurs depends on the intensity of timber harvesting [12].…”
Section: Introductionmentioning
confidence: 99%